Health Literacy and Health Care Utilization in Austria - Andreas Kvas; Gregor Kvas (SLACK Incorporated, 2023)
Background: Efficient use of health care is crucial for health care systems; the literature reveals that health literacy (HL) plays an important role in health services utilization. Objective: This study aimed to analyze the relationship between HL and health care utilization in Austria. Methods: Registered data of 1,010 persons in the general population concerning costs of doctor visits, medication costs, and number, days, and costs of hospitalization were analyzed using a cross-sectional design for the observation period 2017 to 2019. HL was measured as general, digital, and navigational HL using the Austrian part of the European Health Literacy Survey between March 2020 and May 2020. Multivariable two-part hurdle regressions with generalized linear models, considering sociodemographic variables and chronic illnesses, were conducted to investigate the relationship between HL and health care utilization. Key Results: Navigational HL had a significant negative effect on the odds of causing costs at general practitioners, not adjusting (b = −0.02) and adjusting (b = −0.01) for sociodemographic variables and chronic illnesses. The effect was small, and no significant effect on any other type of analyzed health care was found. Conclusions: Further research on specific populations (e.g., persons with chronic diseases such as diabetes), rather than the general population, may reveal relevant effects of HL on health care utilization measured by registered data in Austria. [HLRP: Health Literacy Research and Practice. 2023;7(4):e197-e206.]